Total proximal tibial osteotomy and cranial closing wedge ostectomy for treating concomitant medial patellar luxation and cranial cruciate ligament disease in dogs with excessive tibial torsion - Alefe Luiz Caliani Carrera; Eloy Henrique Pares Curuci; Dayvid Vianêis Farias Lucena; Lucas Vasconcelos Costa; Rodrigo Carvalho de Souza Faustino; Stefânia Carolino Claudino Silva; Luis Gustavo Gosuen Gonçalves Dias; Bruno Watanabe Minto (PLoS ONE, 2025)
Medial patellar luxation (MPL) and cranial cruciate ligament disease (CCLD) frequently co-occur in dogs, with excessive tibial torsion adding surgical complexity. This study evaluates the clinical outcomes of total proximal tibial osteotomy (tPTO) combined with cranial closing wedge ostectomy (CCWO) for treating MPL and CCLD in dogs exhibiting excessive external tibial torsion. A retrospective case series was conducted at a single referral hospital, including dogs with concomitant MPL and CCLD, exhibiting external tibial torsion ≥20°, and treated with tPTO and CCWO. A total of 31 patients met the inclusion criteria. Postoperatively, tibial torsion was corrected in all cases, with 74.2% (n = 23) achieving near 0° alignment. The tibial plateau angle decreased from 23.0° ± 5.0° to 7.0° ± 3.4°. Antirotational techniques were used to prevent reluxation in 25.8% (n = 8) of cases because of stifle soft tissue laxity. The initial success rate for patellar and stifle stability was 87.1%, whereas 12.9% (n = 4) of cases exhibited patellar reluxation, necessitating surgical reintervention with antirotational techniques. Bone healing averaged 70.2 ± 21.2 days, aligning with full clinical recovery. Following the four surgical reinterventions, all patients achieved patellar and stifle dynamic stability with normal weight bearing. The combination of tPTO and CCWO proved effective for treating concomitant MPL and CCLD in dogs with excessive tibial torsion, demonstrating favorable outcomes and complication rates. This technique should be considered for managing these complex cases.